Characterization of HCl-activated Water Hyacinth (Eichhornia crassipes) Adsorbent in Removing Lead Ion (Pb2+) from Battery Industry Effluent - Utami, Wasistianna; Sari, Dessy Agustina; Wahyuningtyas, Aulia (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
This study utilizes the adsorption process to reduce the concentration of lead ions in battery industry wastewater by using adsorbents from water hyacinth (Eichhornia crassipes). This research aims to determine the ability of a bioadsorbent activated by a 0.1 M HCl solution to adsorb Pb2+ through FTIR and AAS characterization. The bioadsorbent was contacted into a standardized solution of Pb2+ with varying contact times (viz., 20, 30, 40, 50, 60, 70, 140, 210, and 280 to determine the maximum adsorption). The highest absorption of the Pb2+ in battery industry wastewater took place for 210 minutes. The absorption ability was 94.45%, with 8.1488 ppm as the initial concentration. Then, this study shows that this characterization before the activation of 0.1 M HCl has O-H, C-H, C=O, and C-O ether functional groups. All three identified the presence of cellulose. Post-activation, lignin, and hemicellulose disappeared due to the vibration of the C=O group. However, an increase in the intensity of the vibrational peak at the C-O group indicates the presence of carbon chain linking in cellulose. Finally, after contact with battery industry effluent, bending vibrations were lost because the H atoms in the functional groups had been substituted with Pb2+.